FAKTOR RISIKO IBU DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI PRAKTIK MANDIRI BIDAN (PMB) DEWI ARIYANI, S.ST - Misna Tazkiah; Isti Qomah; Siti hardiyanti; Siti Aisyah Solechah; Nurul Hidayah (PT. Intelek Cendikiawan Nusantara, 2024)
Anemia in pregnancy is a clinical problem that is often encountered in developing countries. Anemia in pregnancy is a global major concern because it results in increased incidence of mortality and morbidity for mothers and infants. There are still anemic pregnant women whose gestational age and parity are different. This study aimed to analyze the risk factors associated with the incidence of anemia in pregnant women at the PMB of Dewi Ariyani, S.Si.T. This observational study used a case control approach with a case:control ratio of 1:2. A total of 36 research samples participated in this study, consisting of 12 people in the case group and 24 in the control group. Data were analyzed using the chi-square test with an α of 0.05. The results showed that the most pregnant women (83.3%) were 20-35 years and did not work (79.2%). Parity was associated with the incidence of anemia in pregnant women (p=0.012; OR 9.000; 95% CI: 1.817-44.591), and gestational age was also associated with the incidence of anemia (p=7.286; OR 9.000; 95% CI: 1.508-35.211). Besides taking blood supplement tablets regularly, pregnant women with anemia are also advised to increase the consumption of foods that contain iron, such as green-leafy vegetables.